AUDIT OF PAYMENTS ON WAGES - O. Dyakonova; E. Goryunova (Вестник университета)
The article reflects the main challenges facing the organization in the process of building a cost-based system of remuneration of staff. The urgency and importance of the audit of payments of wages, in order to meet the interests of workers and employers in the framework of the current legislation. Analyzed the main sources of information in which the audit is performed calculations on a payment. The recommendations of auditors for violations that can occur with the incorrect bookkeeping of wages.